Community Participation for Adaptation and Mitigation of Climate Change: Case study the implementation of Program Kampung Iklim (Proklim) - Safrina Safrina; Nellyana Roesa; Rizanna Rosemary (Batulis Civil Law Review, 2022)
Community is the most vulnerable to climate change. Engaging community is an important factor for the effectiveness and efficiency of the climate change policy and Proklim is one of solutions to implement it. Proklim is regulated through the Minister of Environment and Forestry Regulation Number P.84/MENLHK-SETJEN / KIM.1 / 11/2006 concerning the Climate Village Program and the regulation of the Director General of Climate Change Control No. P.1/PPI/SET/KUM.1/2/2017 concerning Climate Change Guideline. This study aims to analyze the forms of community participation in Proklim. The method used is a qualitative method with a juridical-empirical approach. The study found that the implementation of Proklim uses a top down approach, where the program was born not based on community initiation but came from the government, the community only acted as program beneficiaries without being actively involved. Mitigation programs are generally developed than adaptation programs. In addition, it is important to create an engaging mechanism. The existence of community groups and community leaders and the availability of supporting tools are important factors in creating the sustainability of ProKlim. This program is expected to increase public understanding of climate change and its impacts, so that lifestyle changes can adapt to it.